Comparative evaluation of the lipid profile in the serum of patients with type II diabetes mellitus and healthy individuals with periodontitis - Thomas, Biju; Prasad, RajendraB; Shetty, Sucheta; Vishakh, R (Contemporary clinical dentistry, 2017)
Periodontal disease is an immuno-inflammatory disease that is initiated by the interaction between microbial plaque and the periodontal tissues. The data available on the association of periodontal diseases with the lipid profile are conflicting. Therefore, a need for a study in this area was felt. To evaluate the lipid profile in the serum of patients with chronic periodontitis and chronic periodontitis with Type II diabetes mellitus (DM) patients and to compare it with healthy controls, to see whether they can serve as potential markers for chronic periodontitis and also to assess whether periodontitis can have systemic effects. This study is a cross-sectional study. This cross-sectional study was conducted involving 300 participants in the age group of 30-60 years from October 2010 to May 2015. Five milliliters of venous blood was collected from each of the study participants, from the antecubital vein. Lipid profile was assessed using the ERBA commercially available kit. Statistical analysis was carried out using SPSS software version 17. Multigroup comparison was carried out using ANOVA. The honest significant difference Tukey's test was used in conjunction with ANOVA to find means which are significantly different from each other. When the lipid profile was estimated, total cholesterol (TC) levels were seen to be significantly higher ( < 0.001) in the DM with periodontitis group. High-density lipoprotein (HDL) levels were seen to be significantly higher ( < 0.001) in the control group. Mean serum low-density lipoprotein (LDL) and very LDL (VLDL) levels were seen to be significantly higher ( < 0.001) in the DM with periodontitis group. The triglyceride (TGL) values were also significantly higher ( < 0.001) in the DM with periodontitis group. The HDL and LDL levels were seen to be nonsignificant between chronic periodontitis and chronic periodontitis with diabetic group. The findings of the study showed that the lipid profile was significantly altered in patients with chronic periodontitis as compared to healthy controls. There was a potentiated difference in the values for TC, VLDL cholesterol, and TGL in patients with chronic periodontitis when compared to patients with Type II DM. HDL cholesterol and LDL cholesterol did not show a significant difference.